2016
DOI: 10.1039/c5cc09718e
|View full text |Cite
|
Sign up to set email alerts
|

Versatile synthesis of cationic N-heterocyclic carbene–gold(i) complexes containing a second ancillary ligand. Design of heterobimetallic ruthenium–gold anticancer agents

Abstract: We describe a versatile and quick route to cationic gold(I) complexes containing N-heterocyclic carbenes and a second ancillary ligand (such as phosphanes, phosphites, arsines and amines) of interest for the synthesis of compounds with potential catalytic and medicinal applications. The general synthetic strategy has been applied to the preparation of novel cationic heterobimetallic ruthenium(II)-gold(I) complexes that are highly cytotoxic on renal cancer Caki-1 and colon cancer HCT 116 cell lines while showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 30 publications
2
65
0
Order By: Relevance
“…Interestingly, within the scope of achieving heteronuclear cytotoxic organometallics, in 2016 Contel et al described a simple and efficient synthetic method to obtain Au(i)-NHCs featuring a second ancillary ligand (such as phosphanes, phosphites, arsines and amines) starting from the chlorido precursor by abstraction of the chloride with silver perchlorate, and subsequent addition of the ancillary ligand. [34] This synthetic strategy has been successfully applied in the preparation of a family of cationic heterobimetallic Au(i)-Ru(ii) complexes (14a-d, Fig. 2).…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…Interestingly, within the scope of achieving heteronuclear cytotoxic organometallics, in 2016 Contel et al described a simple and efficient synthetic method to obtain Au(i)-NHCs featuring a second ancillary ligand (such as phosphanes, phosphites, arsines and amines) starting from the chlorido precursor by abstraction of the chloride with silver perchlorate, and subsequent addition of the ancillary ligand. [34] This synthetic strategy has been successfully applied in the preparation of a family of cationic heterobimetallic Au(i)-Ru(ii) complexes (14a-d, Fig. 2).…”
Section: Anticancer Agentsmentioning
confidence: 99%
“…It is reported that the compound remains cytotoxic even when the glucose membrane transporter, GluT‐1 is inhibited, thereby suggesting that the sugar moiety does not facilitate cellular uptake through the GluT‐1 transporter and that the improved activity of the complex can possibly be ascribed to improved physicochemical properties rather than targeted therapy . Regarding solution stability, complexes 31 – 36 , 43 and 44 were shown to be stable in the presence of DMSO and various buffer solutions for at least 48 hours , , . The stability of the other complexes were not reported.…”
Section: Rutheniummentioning
confidence: 99%
“…However, incorporation of the NHC moiety did not result in stronger DNA interactions as originally hoped for. True synergism was also not demonstrated since the combination of the mononuclear compounds was not evaluated …”
Section: Rutheniummentioning
confidence: 99%
“…Isocyanide metal complexes are used as polymerization catalysts [22], as molecules for one-dimensional electric conductors [23], and as metallomesogens that behave as liquid crystals [24]. Furthermore, isocyanide metal complexes are precursors of carbene complexes [25], which are also catalytic systems [26], and very useful materials for therapeutic applications [27]. Surprisingly, the great potential of isocyanide derivatives has not been exploited to modulate the properties of PDI systems.…”
Section: Introductionmentioning
confidence: 99%